Robotic‐assisted coronary artery bypass surgery: an 18‐year single‐centre experience. Issue 3 (19th January 2018) - Giambruno, Vincenzo; Chu, Michael W.; Fox, Stephanie; Swinamer, Stuart A.; Rayman, Reiza; Markova, Zarina; Barnfield, Rebecca; Cooper, Mitchell; Boyd, Douglas W.; Menkis, Alan; Kiaii, Bob
Abstract: Background: Minimally invasive robot‐assisted direct coronary artery bypass (RADCAB) has emerged as a feasible minimally invasive surgical technique for revascularization that might offer several potential advantages over conventional approaches. We present our 18‐year experience in RADCAB. Methods: Between February 1998 and February 2016, 605 patients underwent RADCAB. Patients underwent post‐procedural selective graft patency assessment using cardiac catheterization. Results: The mortality rate was 0.3%. The rate of conversion to sternotomy for any cause was reduced from 16.0% of the first 200 cases to 6.9% of the last 405 patients. The patency rate of the LITA‐to‐LAD anastomosis was 97.4%. Surgical re‐exploration for bleeding occurred in 1.8% of patients, and the transfusion rate was 9.2%. Average ICU stay was 1.2 ± 1.4 days, and average hospital stay was 4.8 ± 2.9 days. Conclusions: Robot‐assisted coronary artery bypass grafting is safe, feasible and it seems to represent an effective alternative to traditional coronary artery bypass grafting in selected patients.